Optimizing Local Resources for Stunting Prevention and Community Health Promotion in Indonesia: A Mixed-Methods Study on Collaborative Communication and Extension - Ninuk Purnaningsih; Eny Palupi; Sulassih Sulassih; Anita Primaswari Widhiani (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Stunting remains a major public health concern, particularly in rural areas with limited institutional capacities. This study introduces a novel application of the Resource-Based View (RBV) framework in the context of community health in rural Indonesia, integrating local resource optimization, collaborative communication, and institutional extension to enhance the role of Posyandu cadres in preventing stunting. Methods: This mixed-methods study, using a pre-post-test design combined with qualitative triangulation, was conducted between February and August of 2024. The study involved structured learning needs assessments followed by mentoring interventions. Data were collected from a purposive sample of 30 cadres, 9 female leaders, and 57 toddler mothers in selected rural communities through focus group discussions, participatory assessments, interactive feedback sessions, and quantitative pre-post evaluations. Results: The intervention improved the Posyandu cadres’ competencies in nutrition counseling, healthy food preparation, public speaking, and counseling. Structured collaborative communication between cadres, community leaders, and healthcare professionals enhances coordination and aligns training with community needs. Notably, the integration of digital platforms, such as WhatsApp, facilitated ongoing mentoring, wider outreach, and program continuity. Participatory mechanisms further increased program responsiveness and sustainability, whereas local leadership engagement strengthened institutional legitimacy and community ownership. Conclusion: This study demonstrates that collaborative communication, capacity building, and institutional support effectively strengthen the role of Posyandu cadres in preventing stunting by improving both technical and communication skills. By integrating the Resource-Based View (RBV), collaborative communication, and institutional extension frameworks, this study offers a novel and scalable model for optimizing local resources and designing context-specific empowerment programs in resource-limited rural settings. However, the limitations include the small sample size, rural focus, and absence of a control group, indicating the need for larger randomized controlled trials and further research on long-term sustainability.